Do 18F-FDG PET/CT Parameters in Oropharyngeal and Oral Cavity Squamous Cell Carcinomas Indicate HPV Status?. (March 2015) - Kendi, Ayse Tuba Karagulle; Magliocca, Kelly; Corey, Amanda; Nickleach, Dana C.; Galt, James; Higgins, Kristin; Beitler, Jonathan J.; El-Deiry, Mark W.; Wadsworth, J. Trad; Hudgins, Patricia A.; Saba, Nabil F.; Schuster, David M.
Abstract : Objective: The aim of this study was to explore the relationship of PET/CT parameters with human papillomavirus (HPV) status of oropharyngeal (OP) and oral cavity (OC) squamous cell carcinomas (SCCs). Patients and Methods: We retrospectively reviewed 39 patients with OC and OP-SCC who underwent staging 18 F-FDG PET/CT. PET/CT parameters were measured for the primary tumor and the hottest involved node, including SUVmax, SUVmean, SUVpeak, metabolic tumor volume, total lesion glycolysis, standardized added metabolic activity (SAM), and normalized SAM. Patient characteristics were compared between HPV positive (HPV+) and negative (HPV−) groups. Receiver operating characteristic analysis was used to dichotomize PET/CT parameters into high and low. Logistic regression models predicting HPV status were fit for each PET/CT parameter. Results: The HPV+ group was composed of 18 patients all with OP-SCC; the HPV− group consisted of 21 patients, 4 OP cancer patients and 17 OC cancer patients. The HPV+ group had a higher proportion of N2 stage (94% vs 43%; P < 0.001). Nodal PET/CT parameters were higher in the HPV+ group ( P < 0.01); this difference was not present for the primary lesion. After adjusting for sex and age, the association of higher nodal SUVmax (odds ratio [OR], 9.67), SUVmean (OR, 10.48), SUVpeak (OR 9.67), metabolic tumor volume (OR, 14.52), total lesion glycolysis (OR, 11.84), and SAM, normalized SAM (OR, 16.21) with HPV+ status remained statistically significant ( P < 0.05). Conclusions: Nodal PET/CT parameters predict HPV status. High nodal FDG uptake should raise suspicion for positive HPV status in the evaluation of the primary lesion.